Investigation On Processing Parameter Of Single Screw Extrusion Using Experimental And Numerical Approach - Mohd Shah, Mohd Faizatul Shahrizal (Universiti Sains Malaysia, 2018)
Extrusion is one of the common process used in plastic processing that has been used in the industry. But this process needs a lot of consideration from the processing parameter to overcome the problem such as die swell and flow instability. This study were carried out to investigate the effect different temperatures setup and varies screw speed on the Low Density Polyethylene (LDPE) extrudate. Also in this research aimed to visualise the flow behaviour of the polymer melt in the extrusion process by using finite volume analysis. Three dimensional (3D) simulation of polymer rheology in a single screw extrusion was used. In this simulation, the ANSYS FLUENT 15.0 software was used to verify the viscosity model (Cross model). This study determined the effect of process parameter on die swell behavior. Simulation was carried out at different temperatures and screw speeds. Then, an experimental approach were carried out to verify the result from the simulation. The temperature and screw speed was found to be affecting the die swell ratio. The effect of increasing the temperature showed the increment in the die swell ratio. Besides, the effect of screw speed showed that the increasing screw speed increase the die swell ratio up to 1.4 to 1.8. The effect of process parameter such as temperature and screw speed were found to have prominent influences on the viscosity of the LDPE melts. Other than that, the temperature profile of the extrudate were observed both from experimental and simulation and revealed significant results. Simulation study of flow of polymer had to consider various parameters. The strength of ANSYS FLUENT 15.0 in handling simulation of extrusion process needs to be studied in detail in order to produce an accurate and precise result.